Kedudukan Izin Lingkungan Dalam Sistem Perizinan Di Indonesia - Helmi ' (Fakultas Hukum Universitas Riau, 2010)
As an instrument of environmental resource mana-gement, environmental permits has an importantposition. Lay No. 32 of 2009 on the Protection andEnvironmental Management (UU-PPLH) permits theintegration of various environmental permits beforesplitting. But the problems faced, it turns out, the lawit self is still not firmly UU-PPLH provide the scopeand type environmental permit it self. Status ofenvironmental permits for a business license or acti-vities appear on the scope and legal relations of both,which is an instrument of obtaining environmentalpermits and business licenses or implement environ-mental management activities.